Versican facilitates chondrocyte differentiation and regulates joint morphogenesis - Kanyamas Choocheep (2018)
Versican/PG-M is a large chondroitin sulfate proteoglycan in the extracellular matrix, which is transiently expressed in mesenchymal condensation areas during tissue morphogenesis. Here, we generated versican conditional knock-out mice Prx1-Cre/Vcanflox/flox, in which Vcan is pruned out by site-specific Cre recombinase driven by the Prx1 promoter. Although Prx1-Cre/Vcanflox/floxmice are viable and fertile, they develop distorted digits. Histological analysis of newborn mice reveals hypertrophic chondrocytic nodules in cartilage, tilting of the joint, and a slight delay of chondrocyte differentiation in digits. By immunostaining, whereas the joint interzone of Prx1-Cre/Vcan+/+shows an accumulation of TGF-β, concomitant with versican, that of Prx1-Cre/Vcanflox/floxwithout versican expression exhibits a decreased incorporation of TGF-β. In a micromass culture system of mesenchymal cells from limb bud, whereas TGF-β and versican are co-localized in the perinodular regions of developing cartilage in Prx1-Cre/Vcan+/+, TGF-β is widely distributed in Prx1-Cre/Vcanflox/flox. These results suggest that versican facilitates chondrogenesis and joint morphogenesis, by localizing TGF-β in the extracellular matrix and regulating its signaling. © 2010 by The American Society for Biochemistry and Molecular Biology, Inc.